"Already/Not Yet": St Paul's Eschatology and the Modern Critique of Historicism. (November 2018) - Paipais, Vassilios
This paper interrogates some prominent post-Marxist engagements with St Paul's messianism by reading them in the theological context of the anti-historicist revival of Pauline eschatology in the twentieth century. In both readings, the means through which the critique of historicism is delivered is the revival of the eschatological core of Paul's proclamation. Paul is read as inaugurating a "new world" of freedom, love and redemptive hope as opposed to the "old world" of oppression, sorrow, death and despair. And yet, it is exactly in such an apocalyptic reading of Pauline eschatology that both philosophical and theological critiques of historicism, despite protestations to the contrary, remain prisoners to the aporias of a historicist temporality. The symptom of the philosophers' residual parasitism on historicism is expressed as antinomian negativism, while in the case of the theologians it can take the form of a self-assured Church triumphalism.